Researches and optimization of characteristics of an entrance branch pipe of the axial compressor of gas-turbine power installation GTP-110 - Михайлов, В.Е.; Хоменок, Л.А.; Шерапов, В.В.; Нечкин, Б.В.; Рябов, Н.А.; Гасуль, М.Р. (Eastern-European Journal of Enterprise Technologies, 2010)
The report presents the complex study results on aerodynamic, energetic and dynamic (surging) characteristics of axial compressor inlet manifold in the GTI of GTE-110 power plant on the basis of physical process modeling in its elements. The value of inlet manifold energy losses has been assessed and the design solutions aimed at reducing the value and making it possible to decrease these losses significantly have been adopted.